2017
DOI: 10.1186/s12913-017-2707-0
|View full text |Cite
|
Sign up to set email alerts
|

The determinants and consequences of adult nursing staff turnover: a systematic review of systematic reviews

Abstract: BackgroundNurses leaving their jobs and the profession are an issue of international concern, with supply-demand gaps for nurses reported to be widening. There is a large body of existing literature, much of which is already in review form. In order to advance the usefulness of the literature for nurse and human resource managers, we undertook an overview (review of systematic reviews). The aim of the overview was to identify high quality evidence of the determinants and consequences of turnover in adult nursi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
289
3
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(346 citation statements)
references
References 55 publications
(140 reference statements)
25
289
3
8
Order By: Relevance
“…This finding was consistent with Cowden and Cummings' theory. Additionally, a systematic review about the determinants and consequences of nursing staff turnover revealed that job satisfaction/dissatisfaction was the decisive factor affecting the ITS/leave (Halter et al, ). In this study, similar conclusions were reached.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was consistent with Cowden and Cummings' theory. Additionally, a systematic review about the determinants and consequences of nursing staff turnover revealed that job satisfaction/dissatisfaction was the decisive factor affecting the ITS/leave (Halter et al, ). In this study, similar conclusions were reached.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite this, the sense of altruism found amongst nurses can serve to satisfy them (Nasrabadi et al , ). It remains the case, however, that without adequate support and attention from the hospital authorities, nurses can experience decreased levels of job satisfaction, which can then lead to increased levels in intention to leave their employment (Halter et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Although many factors contribute to nursing shortages, high nurse turnover is considered to be one of the major contributors (Sokhanvar et al , ; Tourani et al , ). Turnover is not consistently defined in the literature (Halter et al , ), with descriptions ranging from the actual leaving of the organization to an intent to leave in the near future (Mazurenko et al , ). It has been defined as any career move, whether that move is external, such as when nurses leave the profession or an organization entirely, or internal, when nurses move between nursing units in the same hospital (Duffield et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…In turnover research, work attitudes have been frequently investigated; for example, job satisfaction and organizational commitment have been reported to be connected to quality nursing performance and job retention (Ahmad, Ahmad, & Shah, ; Halter et al, ). Nurses who are satisfied with their tasks, their work environments and the ways they are treated by their organizations are likely to feel a deeper connection to their organizations and accordingly increase their organizational commitment (Benevene et al, ; Chang, ).…”
Section: Introductionmentioning
confidence: 99%